Dynamics of Position of Public Relations of Company Media PT. Lativi Media Karya (Tv One) in Dealing with Hoax Information - Nikmatus Sholikah; Maulina Pia Wulandari; Anang Sujoko (International Journal of Science and Society, 2021)
Hoaxes or false information are now increasingly easy to find in various social media and public information media, this is a challenge for the mass media industry. Hoax information connected globally via the internet can harm various fields of the company, including mass media companies or the press. The purpose of this research is to find out how the dynamics of Public Relations (PR) media company PT Lativi Media Karya or tvOne in overcoming hoax information that is detrimental to the company and what contingent factors affect the attitude of PR tvOne to solve the hoax problem. The object of research used three cases of hoax information which were quite viral in 2016, 2018 and 2020. The Contingency of Accomodation theory is the main theory used to find out the dynamics of the PR position. The research methodology used is a qualitative approach, data collection using two methods, namely semi-structured interviews and documentation, data analysis techniques using constant comparability. The result is that PR tvOne tends to lead to an advocacy positions in overcoming hoax information, even though in the case of hoax information in 2018, it is accommodation in advocacy by withdrawing demands from the police, but PR tvOne still fully defends the company or its advocacy attitude. Then, on the contingent factors in the predisposing and situational variables, each of which has six contigens, it turns out that all of the contaminants affect the PR attitude of tvOne. Researchers found two new important content for media company tvOne, namely "image" and "credibility".